(untitled) (Comprehensive Journal of Science, 2025)
Direct Torque Control DTC is a prominent high-performance control strategy for induction motor IM derives, prized for its rapid dynamic response and structural simplicity. However, classical DTC is plagued by inherent drawbacks, including significant torque and flux ripple, variable switching frequency, and high current total harmonic distortion THD. This paper presents a comprehensive comparative analysis of classical DTC against two modern variants: DTC with Space Vector Modulation (DTC-SVM) and Fuzzy Logic Control-based DTC (DTC-FLC). The performance evaluation is conducted through high-fidelity MATLAB/Simulink models under identical operating conditions. Key Performance Indicators KPIS such as torque ripple, flux ripple, stator current THD, and dynamic response are rigorously analyzed. The results demonstrate the superior performance of modern DTC techniques. DTC-FLC achieves a remarkable 87.5% reduction in torque ripple and stator current THD of only 2.18%, alongside improved transient performance by mitigating overshoot. DTC-SVM offers a robust alternative with a 70.9% torque ripple reduction and stator current THD of 4.12%, besides a fixed switching frequency. The study concludes with application-based recommendations, guiding the selection of the optimal DTC strategy for specific industrial needs